Pengaruh Penambahan Antioksidan Simplisia Kunyit Terhadap Angka Peroksida Minyak Kacang Tanah - Yuniarti Dewi Rahmawati (Eksergi, 2021)
Peanut oil is a peanut product that is used for the food industry. The high content of fatty acids in the form of oleic acid causes peanut oil to break down easily, so it is necessary to add antioxidants to inhibit the oxidation process.The natural antioxidant used is turmeric. The purpose of this study was to determine the effect of the addition of turmeric antioxidants on the peroxide rate of peanut oil. The research method for calculating the peroxide number uses iodometric titration. The results showed that the greater the concentration of turmeric simplicia added to peanut oil, the greater the antioxidant activity. The greatest antioxidant activity was obtained from the weight of simplicia 0.4 g with a long immersion period of 7 days, which resulted in a peanut oil peroxide value of 14.5 ml N / gr.